Ovarian preservation for premenopausal women with early-stage endometrial cancer: a Chinese retrospective study. Issue 6 (June 2019) - Lyu, Tianjiao; Guo, Lu; Chen, Xiaojun; Jia, Nan; Gu, Chao; Zhu, Menghan; Zhao, Yuqing; Liu, Xiaoxia; Feng, Weiwei
Objective: This study aimed to retrospectively investigate the safety of ovarian preservation of premenopausal women with stage 1a endometrial carcinoma. Methods: We performed a population-based study to identify surgically treated stage Ia endometrial cancer of premenopausal women who were diagnosed between August 1989 and December 2015 in our center. Survival outcomes and recurrence rate were examined for premenopausal women who underwent ovarian preservation. Recurrence-free survival rates were calculated following generation of Kaplan–Meier curves and were compared with the log-rank test. Cox regression analysis was performed to identify the independent factors affecting the recurrence rate. Results: Patients with ovarian preservation tended to be significantly younger at diagnosis, have less myometrial invasion, and were less likely to undergo lymphadenectomy compared with women treated with bilateral salpingo-oophorectomy. There was no significant difference in recurrence-free survival between the two groups. In the Cox regression model, ovarian preservation remained an independent prognostic factor for improved overall survival. Conclusion: Ovarian preservation does not have a negative effect on oncological outcomes. Ovarian preservation can be applied to premenopausal women with stage Ia endometrial carcinoma.